Bad Kitty: Party Animal #17 - Bruel, Nick (New York : Roaring Brook Press, 2025)
"It's Puppy's birthday and Kitty would rather be anywhere else. While Puppy gets a BIG present and a very special birthday breakfast, all Kitty can do is pop the balloons, topple the cake, and cause mayhem...unless, she can learn how to let Puppy have the spotlight. Help Puppy (and Kitty) celebrate this special day in this graphic novel about sibling rivalry, and learning how to share, in the latest full-color addition to the bestselling Bad Kitty series. Bad Kitty graphic novel series," -- ONIX annotation.
new kids book 2024 winter.
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Parties -- Comic books, strips, etc; Graphic novels